2021
DOI: 10.1071/ch20354
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chained Pyridinium

Abstract: Two types of long-chained pyridinium N-chloramines were designed and synthesised by covalent linking a N-chloramine unit and a long intact alkyl chain via varied alkylation of 3-hydroxypyridine. Preliminary antibacterial tests showed that both synthetic pyridinium N-chloramines exerted distinctively elevated biocidal efficacy in contrast to previously reported pyridinium N-chloramines that lack a long chain. Such enhanced bactericidal behaviour was probably caused by ‘synergistic’ biocidal action between the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The highlight of the synthesis route based on 21 is the elevated total yield (from 20% to 60%) as well as the overall simplified procedure without ion exchange. 9–12 Such observations (including 13 C NMR spectra in Fig. S5, ESI†) together with HRMS data, evidently implied the successful chlorination.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…The highlight of the synthesis route based on 21 is the elevated total yield (from 20% to 60%) as well as the overall simplified procedure without ion exchange. 9–12 Such observations (including 13 C NMR spectra in Fig. S5, ESI†) together with HRMS data, evidently implied the successful chlorination.…”
mentioning
confidence: 76%
“…S1, ESI†). According to previous reports, 9–13 the electron-withdrawing inductive (EWI) effect of the new N–Cl bond causes a specific downfield chemical shift, obvious in the NMR spectra. For instance, the –CH 3 signal shifted downfield from 1.28 ppm to 1.45 ppm, and the –CH 2 – signal shifted downfield from 3.91 ppm to 4.50 ppm (Fig.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…As expected, 21 realized total kill of S. aureus and E. coli within 5 minutes, indicating the best antibacterial performance of this serie. Based on superior bactericidal efficacy of long-chained sulfonium N-chloramines and long-chained pyridinium Nchloramines, [9,15] it could be preliminarily concluded that the presence of an structral intact long chain (e. g. À C 12 H 25 ) is indispensable for the highly efficacious biocidal performance due to "synergistic" antibacterial actions between the two respective bacteriacidal units of N-Cl scaffold and QA salt moiety. Given that the specific charge remains constant (Figure 1, m + n = 13) and that the methylene linker length ChemistrySelect increases (n increases), the length of intact chain essentially decreases (m decreases).…”
Section: Chemistryselectmentioning
confidence: 99%